The physical environmental conditions for biogeochemical differences along the Antarctic Circumpolar Current in the Atlantic Sector during late austral summer 2012. (April 2017) - Strass, Volker H.; Leach, Harry; Prandke, Hartmut; Donnelly, Matthew; Bracher, Astrid U.; Wolf-Gladrow, Dieter A.
Abstract: The physical and biological carbon pumps in the different hydrographic and biogeochemical regimes of the Atlantic Sector of the Southern Ocean are controlled by a series of coupled physical, chemical and biological processes and a project named Eddy-Pump was designed to study them. The Eddy Pump field campaign was carried out during RV Polarstern Cruise ANT-XXVIII/3 between January and March 2012. Particular emphasis was laid on the differences which occur along the axis of the Antarctic Circumpolar Current (ACC) with its associated mesoscale eddy field. The study sites were selected in order to represent (1) the central ACC with its regular separation in different frontal jets, investigated by a meridional transect along 10°E; (2) a large-scale bloom west of the Mid-Atlantic Ridge which lasted several months with conspicuous chlorophyll-poor waters to its immediate east studied by a three-dimensional mesoscale survey centred at 12°40′W; and (3) the Georgia Basin north of the island of South Georgia, which regularly features an extended and dense phytoplankton bloom, was investigated by a mesoscale survey centred at 38°12′W. While Eddy-Pump represents an interdisciplinary project by design, we here focus on describing the variable physical environment within which the different biogeochemical regimes developed. For describing the physical environment we use measurements of temperature, salinity and density, of mixed-layer turbulence parameters, of dynamic heights and horizontal current vectors, and of flow trajectories obtained from surface drifters and submerged floats. This serves as background information for the analyses of biological and chemical processes and of biogeochemical fluxes addressed by other papers in this issue. The section along 10°E between 44°S and 53°S showed a classical ACC structure with well-known hydrographic fronts, the Subantarctic Front (SAF) at 46.5°S, the Antarctic Polar Front (APF) split in two, at 49.25°S and 50.5°S, and the Southern Polar Front (SPF) at 52.5°S. Each front was associated with strong eastward flows. The West Mid-Atlantic Ridge Survey showed a weak and poorly resolved meander structure between the APF and the SPF. During the first eight days of the survey the oceanographic conditions at the Central Station at 12°40′W remained reasonably constant. However after that, conditions became more variable in the thermocline with conspicuous temperature inversions and interleavings and also a decrease in temperature in the surface layer. At the very end of the period of observation the conditions in the thermocline returned to being similar to those observed during the early part of the period with however the mixed layer temperature raised. The period of enhanced thermohaline variability was accompanied by increased currents. The Georgia Basin Survey showed a very strong zonal jet at its northern edge which connects to a large cyclonic meander that itself joins an anticyclonic eddy in the southeastern quadrant. The water mass contrasts in this survey were stronger than in the West Mid-Atlantic Ridge Survey, but similar to those met along 10°E with the exception that the warm and saline surface water typical of the northern side of the SAF was not covered by the Georgia Basin Survey. Mixed layers found during Eddy-Pump were typically deep, but varied between the three survey areas; the mean depths and standard variations of the mixed layer along the 10°E were 77.2±24.7 m, at the West Mid-Atlantic Ridge 66.7±17.7 m, and in the Georgia Basin 36.8±10.7 m.